The effects of ankle mulligan mobilisation in children with cerebral palsy: a randomized single blind control study - Ratib Shaban Ragheb Abushameh; Güçhan Topcu, Zehra; Ayse Nur Tunal; Akram Amro; Azzam AlArab (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the impact of range of motion changes before and after Mulligan mobilisation with ankle movement interventions on the daily lives of children with diplegic cerebral palsy. Method: The single blind randomised controlled study was conducted from July 30, 2022, to January 10, 2023, at 3 rehabilitation centres in Hebron, Palestine, after approval from the ethics review committee of Eastern Mediterranean University, Northern Cyprus, and comprised children with cerebral palsy, who were randomised into intervention group IG and control group CG. All the subjects received regular physiotherapy sessions, overseen by their parents, while those in group IG received mobilisation with ankle movement treatment 3 times per week for 4 weeks. Post-intervention assessment of ankle range of motion, balance, functional performance and quality of life was done using a goniometer, the timed up and go test, 88-item gross motor function measure, 6-minute walk test and the cerebral palsy quality of life questionnaire. Data was analysed using SPSS 24. Results: Of the 64 patients, 40(63%) were girls, and 24(37%) were boys. The overall age range was aged 4-12 years. There were 32(50%) patients in each of the two groups. Mobilisation with movement had a significant effect on active and passive range of motion for the left and right ankles (p<0.05) as well as on balance, gross motor function and quality of life (p>0.05). However, mobilisation with movement had no significant effect on the the distance covered during the 6-minute walk test (p>0.05). Conclusion: Mobilisation with movement had a significant impact on active and passive ankle range of motion, balance and quality of life in diplegic children with cerebral palsy, but it had no impact on gait function. Clinical trial registration number: The study was registered at the United States National Institutes of Health (ClinicalTrials.gov) with registration number NCT05500924. Key Words: Cerebral palsy, Mobilisation, Range of motion, Function, Quality of life.